1980
DOI: 10.1002/pen.760201206
|View full text |Cite
|
Sign up to set email alerts
|

A basic experimental study of sandwich injection molding with sequential injection

Abstract: An experimental study of sandwich injection molding is reported which involves sequential injection of polymer melts with differing melt viscosity into a mold. In isothermal injection molding the relative viscosity of the two melts is the primary variable determining the phase distribution in the mold. Generally the most uniform skin‐core structure occurs when the second melt entering the mold has a slightly higher viscosity than the first melt injected. Large viscosity inequalities lead to nonuniform skin thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 17 publications
4
31
0
Order By: Relevance
“…Experimental mould filling studies of co-injection moulding have been reported by many authors [4][5][6][7][8][9][10] , showing that the main factors influencing the skin=core distribution are the amount of core and skin material, their relative viscosities, the moulding parameters and, last but not least, mould geometry. The maximum theoretical amount of core material that can be injected without breakthrough is between 65% and 75% in simple axial symmetric parts, and is much lower in more complicated geometries [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Experimental mould filling studies of co-injection moulding have been reported by many authors [4][5][6][7][8][9][10] , showing that the main factors influencing the skin=core distribution are the amount of core and skin material, their relative viscosities, the moulding parameters and, last but not least, mould geometry. The maximum theoretical amount of core material that can be injected without breakthrough is between 65% and 75% in simple axial symmetric parts, and is much lower in more complicated geometries [2] .…”
Section: Introductionmentioning
confidence: 99%
“…In the Volume of Fluid (VoF) method [25,42,50,73] a fractional volume or color function is defined to indicate the fraction of a mesh element that covers a particular type of fluid. Algorithms for volume tracking are designed to solve the equation @c=@t þ r Á ðcuÞ ¼ 0, where c denotes the color function, u the local velocity at the front, t the time and r ¼ ð@=@x 1 ; .…”
Section: Introductionmentioning
confidence: 99%
“…A number of methods have been used for this purpose, such as; front capturing methods (Noh & Woodward, 1976): see e.g. VOF method (Hirt & Nichols, 1981), the method of Young (Young et al, 1980), front tracking methods (Tryggvason & Unverdi, 1990;Tryggvason et al, 2001;Unverdi & Tryggvason, 1992): see e.g. marker and cell method (Aulisa et al, 2004), adaptive front tracking method (Galaktionov et al, 2000) and mapping method (Kruijt et al, 2001a).…”
Section: Introductionmentioning
confidence: 99%